Forensic botany : a practical guide - Hall, David W. [ (David Walter)] , 1940- (Essentials of forensic science (forensic science society), 2012)
Forensic botany : a practical guide is an accessible introduction to the way in which botanical evidence is identified, collected and analysed in criminal cases. Increasingly this form of evidence is becoming more important in forensic investigation and yet there are few trained botanists able to assist in such cases